Pengaruh Kompetensi Sumber Daya Manusia, Pemanfaatan Teknologi Informasi, Komitmen Organisasi dan Penerapan Sistem Pengendalian Intern Pemerintah Terhadap Kualitas Penyusunan Laporan Keuangan - Hadi Hadi; Darwanis Darwanis (Jurnal Telaah dan Riset Akuntansi, 2017)
This study aimed to examine the effect of human resources, utilization of information technology, organizational commitment and implementation of internal control system, either simultaneously or partially on the quality of financial reporting on the work unit area of North Aceh district. The population in this study was the financial administration officials SKPD (KDP-SKPD) and the budget (PA), which amounted to 126 people, with details of financial administration of 63 officials and 63 people SKPD Budget Users. The data used was primary data, data collection techniques for distributing a questionnaire consisting of 51 items statement. The analytical method used was multiple linear regression. Simultaneous research results showed that the variable competence of human resources, utilization of information technology, organizational commitment and implementation of internal control systems jointly influence on the quality of financial reporting work unit area of North Aceh district. The results showed that the variable partial competence of human resources, utilization of information technology, organizational commitment and implementation of internal control systems is partially affected the quality of the financial reporting work unit area of North Aceh district.KEYWORDS : Human resources, information technology, organizational commitment, internalcontrols and the quality of the preparation of financial statements